L'Art depuis 1960. - Archer, Michael (Paris : Thames & Hudson, 1997)
Abramovic, Marina ; Acconci, Vito ; Andre, Carl ; Anselmo, Giovanni ; Araeen, Rasheed ; Arman ; Art & Language ; Asher, Michael ; Atlkinson, Terry ; Aycock, Alice ; Baldessari, John ; Barry, Judith ; Barry, Robert ; Baselitz, Georg ; Basquiat, Jean-Michel ; Becher, Bernd & Hilla ; Benglis, Lynda ; Beuys, Joseph ; Bickerton, Ashley ; Bloom, Barbara ; Boltanski, Christian ; Bourgeois, Louise ; Broodthaers, Marcel ; Buren, Daniel ; Calle, Sophie ; Caro, Anthony ; Chamberlain, John ; Chicago, Judy ; Christo & Jeanne-Claude ; Clemente, Francesco ; Cragg, Tony (Anthony) ; César ; Deacon, Richard ; Douglas, Stan ; Espaliú, Pepe ; Finlay, Ian Hamilton ; Fischl, Eric ; Flanagan, Barry ; Fleury, Sylvie ; Fritsch, Katharina ; Fury, Gran ; Gilbert & George ; Gober, Robert ; Golub, Leon ; Gonzalez-Torres, Felix ; Graham, Dan ; Graves, Nancy ; Guston, Philip ; Haacke, Hans ; Halley, Peter ; Hammons, David ; Haring, Keith ; Hatoum, Mona ; Hesse, Eva ; Hill, Gary ; Hiller, Susan ; Hirst, Damien ; Hockney, David ; Hodgkin, Howard ; Holzer, Jenny ; Horn, Rebecca ; Huebler, Douglas ; Höfer, Candida ; Immendorff, Jörg ; Johns, Jasper ; Judd, Donald ; Kabakov, Ilya ; Kawara, On ; Kelley, Mike ; Kelly, Ellsworth ; Kelly, Mary ; Kiefer, Anselm ; Kienholz, Ed ; King, Phillip ; Kippenberger, Martin ; Klein, Yves ; Koons, Jeff ; Kossoff, Leon ; Kosuth, Joseph ; Kounellis, Jannis ; Kusama Yayoi ; Lawler, Louise ; LeWitt, Sol ; Levine, Sherrie ; Lichtenstein, Roy ; Long, Richard ; Louis, Morris ; Lueg, Konrad ; Lüpertz, Markus ; Manzoni, Piero ; Mapplethorpe, Robert ; Matta-Clark, Gordon ; McCracken, John ; Merz, Mario ; Miss, Mary ; Moore, Frank ; Morley, Malcolm ; Morris, Robert ; Mucha, Reinhard ; Nauman, Bruce ; Newman, Barnett ; Noland, Kenneth ; Oldenburg, Claes ; etc.
boek